2020
DOI: 10.1002/adfm.202006939
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐Site Electrocatalysts Boost pH‐Universal Nitrogen Reduction by High‐Entropy Alloys

Abstract: Electrocatalytic nitrogen reduction reaction (NRR) has been an important area for many scientists. However, high voltage requirements, low NH3 yield, and poor stability remain the biggest challenges for NRR. Here, novel high‐entropy alloys RuFeCoNiCu nanoparticles with small size (≈16 nm) and uniformity, prepared in oil phase at atmospheric pressure and low temperature (≤250 °C) are reported for the first time and are applied to NRR. According to the experiments, there is a high NH3 yield at a low overpotentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
96
1
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 143 publications
(100 citation statements)
references
References 53 publications
1
96
1
2
Order By: Relevance
“…The Cu NPs on cellulose/carbon paper (Cu/cellulose/CP) showed a high ethylene selectivity of 48.92% at a potential of −0.529 V versus the reverse hydrogen electrode (RHE) and stability over 30 hours of reaction in a 10 M KOH electrolyte. This study demonstrated how cellulose enables high surface coverage of metal NPs, which opens the possibility of applying metal NPs and multicomponent NPs to more diverse applications ( 7 , 16 19 ).…”
Section: Introductionmentioning
confidence: 81%
“…The Cu NPs on cellulose/carbon paper (Cu/cellulose/CP) showed a high ethylene selectivity of 48.92% at a potential of −0.529 V versus the reverse hydrogen electrode (RHE) and stability over 30 hours of reaction in a 10 M KOH electrolyte. This study demonstrated how cellulose enables high surface coverage of metal NPs, which opens the possibility of applying metal NPs and multicomponent NPs to more diverse applications ( 7 , 16 19 ).…”
Section: Introductionmentioning
confidence: 81%
“…The compositional and structural diversities of HEAs and HECs give us a new avenue of regulating their surface electronic structures and catalytic performances. Hence, the use of HEA and HEC NPs for electrocatalysis is highly attractive owing to their impressive catalytic activity, excellent selectivity, and good durability 3,46,48,80,81,92–97 . To highlight the potentials of HEAs and HECs, we focus on the discussion of some recent examples of important electrocatalytic reactions, including HER, OER, oxygen reduction reaction (ORR), carbon dioxide reduction reaction (CO 2 RR), nitrogen reduction reaction (NRR), MOR, and ethanol oxidation reaction (EOR).…”
Section: Heas and Hecs For Electrocatalysismentioning
confidence: 99%
“…However, the synthesis of highly efficient and robust electrocatalysts still remains to be a challenge for NRR. For the first time, Wang and coworkers designed a novel quinary HEA (RuFeCoNiCu) NPs with a small size (∼16 nm) and uniformity using the oil phase method at atmospheric pressure and low temperature (≤250 °C) 94 . The synthesized HEA NPs was then applied to the electrochemical NRR and showed extraordinary catalytic activity and stability, with a NH 3 yield rate of 11.4 μg h −1 cm −2 and a Faradaic efficiency of 38.5% at 0.05 V versus RHE in 0.1 M KOH electrolyte (Figures 9G–I).…”
Section: Heas and Hecs For Electrocatalysismentioning
confidence: 99%
“…When multiple H atoms are adsorbed, they are mainly distributed over the hollow positions, and the adsorption energy decreases rapidly with the H coverage. 148 Fig. 7 (a) Schematic depicting functions of Pt/Au@ZIF.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%
“…Copyright 2020, Wiley-VCH. 148 Therefore, the surface H adsorption will affect the Co-Ni-Ni sites, but the optimal site of NRR, t-Fe, is not at a hollow position and will not be affected significantly. Clearly, different metals may play different roles and work in a synergetic way to provide outstanding NRR performance (Fig.…”
Section: Nanoscale Advances Accepted Manuscriptmentioning
confidence: 99%